Editorial. Elits i arquitectura a l'antiguitat tardana. Elites and Architecture in the Middle Ages - Jurković, Miljenko (Array, 2007)
Introductory note on the programme of two international symposia (Barcelona, Motovun) with the proceedings published in Hortus Artium Medievalium. The first one was directed by Gisella Ripoll. The year 2006 saw two complementary colloquia, dealing with the theme of elites and architecture in the period from Late Antiquity to the Middle Ages.